2021
DOI: 10.1063/5.0035631
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-accessibility conditions estimated by plasma parameters obtained experimentally on electron cyclotron resonance ion source

Abstract: We insert two probes in the upstream and the downstream regions with respect to the electron cyclotron resonance (ECR) zone which is formed at the center of mirror fields. We measure simultaneously plasma parameters in those regions by each of them under the same operating condition. We measure ion saturation currents Iis and electron energy distribution functions at two positions. We obtain measurement results that suggest the more efficient ECR on the side closer to the microwave-launchings than those on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…As a result, we observed an increase in multicharged ion currents due to the UHR and simultaneously an increase on the high energy side of electron energy distribution function that supported it [10]. Furthermore, Dual ECR experiment was conducted and the yield of multicharged ions was successfully increased [11].…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…As a result, we observed an increase in multicharged ion currents due to the UHR and simultaneously an increase on the high energy side of electron energy distribution function that supported it [10]. Furthermore, Dual ECR experiment was conducted and the yield of multicharged ions was successfully increased [11].…”
Section: Introductionmentioning
confidence: 67%
“…2.45GHz microwaves for ECR discharge are coaxially converted from the waveguide to the inside of the vacuum vessel via a three-dimensional circuit independently from two magnetron sources with a maximum power of 1.3kW through the waveguide coaxial conversion windows. One is a semi-dipole antenna at the tip of the inner conductor where the mirror magnetic field is at the maximum position after being reduced to a taper shape while keeping the aspect ratio of the inner and outer diameters constant in vacuum and then inserted along the mirror magnetic field from the upstream end side of the mirror at z = -418mm [11]. On the other hand, the microwave power is supplied from the Ti rod antenna from the side of the vacuum vessel on the downstream side near the extraction electrode.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on the gas mixing effect [2] [3], which is known as an empirical method to increase multicharged ions in ECRIS's. In our previous studies, the increase of Ar multicharged ion yield has been confirmed by the upper hybrid resonance (UHR) [4] using 4-6 GHz Xmode microwaves, the dual ECR heating method [5] in which microwaves are fed from two antennas simultaneously. We are attempting to increase the multicharged ions using lower hybrid resonance (LHR) by introducing low frequency electromagnetic waves (radio frequency waves: RF waves).…”
Section: Introductionmentioning
confidence: 83%